Executive functions and cognitive subprocesses in patients with obstructive sleep apnoea - LIS, STEFANIE; KRIEGER, STEPHAN; HENNIG, DOROTHEE; RÖDER, CHRISTIAN; KIRSCH, PETER; SEEGER, WERNER; GALLHOFER, BERND; SCHULZ, RICHARD (Journal of sleep research, 2008)
Summary In recent years, special interest has been focused on impairments of executive functions in patients with obstructive sleep apnoea syndrome (OSAS). However, the majority of studies have not clearly separated deficits in executive functions from impairments in other cognitive processes involved in task solving. In the present study, working memory (WM) functions of 20 patients with OSAS were compared with those of 10 age‐, sex‐ and education‐matched healthy subjects. Cognitive functions were measured four times a day; each of these measurements was accompanied by an assessment of subjective and objective daytime sleepiness. To separate dysfunctions of WM from those of additionally involved processes, n‐back tasks were applied embedded in a reaction‐time‐decomposition approach. Deficits in n‐back tasks could be observed in OSAS patients in accuracy and reaction times. However, the slowing could already be observed in simple reaction time tasks. The drop in 1‐back accuracy in the morning was related to daytime sleepiness. During the afternoon, accuracy of OSAS patients dropped in 2‐back tasks, an effect which correlated neither with sleepiness nor with the extent of sleep apnoea or oxygen desaturation. In conclusion, our data reflect a complex perspective upon cognitive deficits in OSAS. Cross‐group differences in processing time on the higher level WM task appeared to be attributable to slowing at a more elementary cognitive processing level. In contrast, reduced accuracy during the WM task in the OSAS group could not be explained by deficits in more elementary cognitive processes.